Optimizing Collaboration Skills in Vocational Students with Discovery Learning and Project-Based Learning - Kusumaningrum, Hanifah; Harsono, Harsono; Suyatmini, Suyatmini; Haryanto, Sigit; Noorwandani, Yasinta Arizona (Universitas Pendidikan Indonesia, 2024)
Collaboration skills are vital for 21st-century success, particularly as advancements reshape various aspects of life. At SMK N 1 Kedawung, The Basics of Plant Agribusiness, a subject for tenth graders, emphasizes cultivating these skills. This study investigates the effects of different learning models-discovery learning and project-based learning (PjBL)-on enhancing vocational students' collaboration skills. Conducted using classroom action research with a qualitative descriptive approach, the study spanned five cycles. The findings reveal that both models significantly improve collaboration skills. Discovery learning fosters inquiry and problem-solving through active exploration, gradually enhancing teamwork and critical thinking. In contrast, PjBL centers on collaborative, real-world projects, promoting hands-on engagement and deeper learning. Quantitative results show that collaboration skills improved in all cycles, with PjBL demonstrating a more pronounced effect. Discovery learning yielded consistent yet gradual improvements over three cycles. However, PjBL facilitated quicker and more substantial progress within two cycles, underscoring its effectiveness in fostering teamwork, participation, and practical knowledge application. In conclusion, both methods positively influence collaboration skills, with PjBL offering superior outcomes. Its practical, engaging approach makes it particularly effective for vocational training, addressing the demands of 21st-century education. PjBL is thus recommended for optimal skill development.